Why we get fat and what to do about it - Taubes, Gary. (2011)
This work is an examination of what makes us fat. In his book Good Calories, Bad Calories, the author, an acclaimed science writer argues that certain kinds of carbohydrates, not fats and not simply excess calories, have led to our current obesity epidemic. Now he brings that message to a wider, nonscientific audience. With fresh evidence for his claim, this book makes his critical argument newly accessible. He reveals the bad nutritional science of the last century, none more damaging than the "calories-in, calories-out" model of why we get fat, the good science that has been ignored, especially regarding insulin's regulation of our fat tissue. He also answers key questions: Why are some people thin and others fat? What roles do exercise and genetics play in our weight? What foods should we eat or avoid? Concluding with an easy-to-follow diet, this book is one key to understanding an international epidemic and a guide to improving our own health.
The original sin -- Biology, not Physics -- Why were they fat? -- The elusive benefits of undereating -- The elusive benefits of exercise -- The significance of twenty calories a day -- Why me? Why there? Why then? -- Thermodynamics for dummies, part 1 -- Thermodynamics for dummies, part 2 -- Head cases -- Adiposity 101 -- The laws of adiposity -- A historical digression on "lipophilia" -- A primer on the regulation of fat -- Why I get fat and you don't (or vice versa) -- What we can do -- Injustice collecting -- Why diets succeed and fail -- A historical digression on the fattening carbohydrate -- Meat or plants? -- The nature of a healthy diet -- Following through.
"Originally published in hardcover in slightly different form in the United States by Alfred A. Knopf"--Title page verso.
Includes bibliographical references (pages 239-256) and index.
Keywords: Low-carbohydrate diet; Weight loss; Obesity -- Etiology